2021
DOI: 10.1108/rege-02-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Growth and social entrepreneurs: the challenge of conciliating economic and social values

Abstract: PurposeThis research aimed to describe the phenomenon of the growth of enterprises in the vision of social entrepreneurs.Design/methodology/approachThis is a qualitative study developed joining eight social entrepreneurs in four organizations, two cooperatives and two associations. Data were obtained in semi structured interviews. Data were analyzed with interpretativist and the classical content analysis.FindingsThe main findings indicated the growth phenomenon presented in five categories: growth intentions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…Desse modo, determinados conceitos colaboram para o entendimento de que o empreendedorismo, com todas as características, também é cultural e não deve ser empregado e compreendido apenas em seu conceito amplo, uma vez que a cultura do empreendedorismo se constitui também pelas diferenciações culturais entre regiões e organizações (Machado;Basaglia, 2013;Julien;Marchesnay;Machado, 2010).…”
Section: Uma Análise Da Metodologia Do Ensino De Empreendedorismo No ...unclassified
“…Desse modo, determinados conceitos colaboram para o entendimento de que o empreendedorismo, com todas as características, também é cultural e não deve ser empregado e compreendido apenas em seu conceito amplo, uma vez que a cultura do empreendedorismo se constitui também pelas diferenciações culturais entre regiões e organizações (Machado;Basaglia, 2013;Julien;Marchesnay;Machado, 2010).…”
Section: Uma Análise Da Metodologia Do Ensino De Empreendedorismo No ...unclassified
“…First, we present the group of 13 studies that follow a business resource theorization of social capital. In such studies, inter-and intra-organizational success is found to depend on the presence and operation of dynamic business networks [91][92][93][94][95][96], the values that are shared among business and/or network members [97][98][99][100][101], and group trust [102]. In other words, the efficiency of business models that arise from within a social innovation-social goods provisional framework is reduced in the presence of distinct social capital items such as the networks, values, and trust components analyzed in the aforementioned studies.…”
Section: Inter-and Intra-organization Studiesmentioning
confidence: 99%
“…They promote social stability and alleviate poverty in the communities in which they are located. Regarding social enterprises, the emphasis is always placed on combining economic and social values (Pelizza Vier Machado et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%